Turizmin çevresel etkileri ve İznik çevresinde alternatif turizm gelşiminin değerlendirilmesi - Akkaya, Arzu (Fen Bilimleri Enstitüsü, 1994)
Turizmin plansız ve kontrolsüz bir gelişim sürecinde çevre de meydana getirdiği olumsuz değişikliklerin önlenmesi açısından, turizm projelerinin uygulamaya geçirilmeden önce olası çevresel etkilerinin değerlendirilmesi, doğru plan kararları ile desteklenmiş bir turizm gelişiminin ortaya çıkmasını sağlar. Turizm gelişimi de ancak çevrenin doğal ve kültürel değerlerini bozmayan, estetik ve mimari değeri yüksek ve aynı zamanda o çevrenin kimliğini taşıyan bir anlayışla tasarlanan bina ve çevre düzenlemeleri ve çevreye duyarlı turizm türlerinin geliştirilmesi ile başarı olur. Bu amaçla tezin kapsamında tarihi ve doğal değerleri ile turizm yönünden önemli bir potansiyele sahip İznik kent ve göl çevre sinde öneri alternatif turizm gelişimi ve turizm binalarının olası çevre sel etkileri değerlendirilmiştir. Birinci bölüm, konuya giriş niteliğini taşımaktadır. İkinci bölümde, turizm ve çevre arasındaki ilişkiler ele alınarak, turizmin doğal, yapısal ve sosyo-kültürel çevredeki etkileri olumlu ve olumsuz etkiler başlıkları altında incelenmiştir. Üçüncü bölümde, turizmin çevresel etkilerini kontrol önlemleri kapsamında çevresel etkilerin değerlendirilmesi ve bu değerlendirmede kullanılan metodlardan biri olan Delphi tekniği açıklanmakta ve taşıma kapasitesine ve ölçülmesine ilişkin tanımlamalar yapılarak, ülkemizde ve gelişmekte olan ülkelerde çevre korumaya yönelik yasal düzenlemeler incelenmiştir. Dördüncü bölümde, turizmin çevre üzerindeki olumsuz etkilerini önlemek veya azaltmak için ortaya çıkan ve çevreye duyarlı bir tasarım anlayışının içerdiği bir turizm gelişimini hedefleyen alternatif turizm türleri ve ülkemizdeki potansiyeli incelenmiştir. Beşinci bölümde, İznik'te yerleşme bölgesi içinde veya yakınında ve göl çevresinde öneri alternatif turizm gelişiminin ve turizm binalarının doğal, yapısal ve sosyo-kültürel çevredeki etkileri ve ekonomik boyutu; Delphi tekniğinde kullanılan anket formundan yararlanılarak hazırlanmış bir anketin 12 kişilik bir gruba uygulanması ile alınan yanıtlar doğrultusunda değerlendirilmiştir. Son bölümde, yapılan anket çalışmasından elde edilen değerlendirmeler doğrultusunda genel bir sonuca varılmıştır.

In terms of prevention of changes tourism can bring on the environment in the process of uncontrolled and unplanned development, assessment of potential environmental impacts provides that a tourism development supported with proper plan decisions brings light before tourism projects aren't applied. Tourism projects may be successful only with building and environment arrangements designed with the understanding which has high quality aesthetic and architectural characteristics, not destroying natural and cultural values of the environment. In this study, the potential environmental impacts of proposal alternative tourism development and tourism buildings are assessed in İznik city and its lake surroundings. Chapter 1 is an introduction to the subject. Here, the importance of assessment of the environmental impacts of tourism is stressed with reality that changes unplanned and uncontrolled tourism development can bring on the environment can affect considerably tourism resource. In Chapter 2, Relations between tourism and environment are studied generally and the potential pozitive and negative impacts on the natural, built and socio-cultural environments are analyzed. Environment is the whole of natural and artificial conditions, effects and forces which surround living organisms, affects and changes them and at the same time, being in connections. Environment, in general, is a physical environment. Researchs on relations between tourism and environment, have more concentrated natural and built components of physical environment. However, impacts on his cultural environments which effects of man change have gradually importance. Components of environment on which potential impacts from the result of tourism development are studied, are as follows: 1. Natural Environment: It includes topography, air, land, climate, flora and fauna. vu 2. Built Environment: It encompasses all man-made buildings from one building to a complex city, infrastructure, open spaces, archaeological and historical places. 3. Socio-Cultural Environment: It includes the values, beliefs, behaviours, morals, arts, law of community, "high culture" such as opera and ballet, and "popular culture" such as folk, music and craft work. Relations tourism and environment has arise from that environment is the main resource that provides tourism activities make real. Tourism uses environmental resources in two principal ways/Firstly, as primary inputs in to the production of the tourist product (scenery, coasts, mountain, forests) and as sinks for the residuals generated during the production and consumption of this product. Properly planned and controlled tourism development may contribute to conservation and improvement of environment from various aspects. On the other hand, uncontrolled development of tourism and its pressure that consists of excessive man activites, can cause environmental deterioration. Because tourism is an activity which can develop in environmentally sensitive areas, in this section, first of all, impacts on natural and built environments are examined, impacts on socio-cultural environments are handled in the narrow context. Pozitive impacts of tourism on the natural and built environment are grouped as follows: 1. Conservation of natural areas 2. Conservation archaeological and historical sites and architectural characteristics 3. Enhancement of environmental quality 4. Improvement of infrastructure Negative impacts of tourism on the natural and built environment are grouped as follows: 1. Water pollution 2. Air pollution 3. Noise pollution 4. Visual pollution 5. Waste disposal problems 6. Ecological disruption 7. Environmental hazards 8. Damage to archaeological and historical places 9. Land use problems Pozitive impacts of tourism on the socio-cultural environment are grouped as follows: vui 1. Conservation of cultural heritage 2. Cross-cultural exchange Negative impacts of tourism on the socio-cultural environment are grouped as follows: 1. Overcrowding of amenities for residents 2. Loss of authenticity of traditional arts and crafts 3. Changes in behaviour and values In chapter 3, In the context of controlling measures of the environmental impacts, the assessment environmental impacts and the use of Delphi technique, which is one of the method used in this assesment are explained and making definitions related to measurement and of carrying capacity, legislative regulations related to environmental conservation in Turkey and developing countries are studied. The changes which a uncontrolled and unplanned tourism development can cause on the natural, built and socio-cultural environments may reach to such a dimension that specific characteristics of a tourism area attracting tourists may disappear. Prevention of the impacts of tourism not reaching such a dimension is inevitable necessity in terms of sustainable environmental values and the conservation of it. In this context; the assessment of potential pozitive and negative impacts of proposed tourism development on the environment beforehand will be useful in terms of planning of most suitable development for the area. This assessment will affect pozitively the planning on the subject as selection of location, architectural design. This effort of preventing of these impacts of tourism puts on the agenda the application of various control methods. Many countries apply various methods of the assessment of environmental impacts and environmental legislations to prevent or minimize negative impacts of tourism. Assessment of Environmental Impact or analysis studies are one of the important planning instrument in defining beforehand and preventing or minimizing the potential effects from the result of tourism development which is planned to be realized. Delphi technique used in environmental impact analysis was developed by Rand Corporation in the USA in the 1960s as a technique of future forecast. Delphi is a well established judgemental technique used as a means of collecting expert opinion and of working towards consensus between experts on a given issue. The members of panel including twenty persons in general, are chosen among expert persons such as planners, tourism officers, economist, civil engineers, environmental health officers. In Delphi, each participant is answered separetely. Reliability level of using the IX results obtained through use of Delphi depends on the level of specialization of the participants related to the issue examined, responses rates to the questionnaires and interpretation of results. In addition to application of controlling methods of environmental impact, determination of carrying capacity and application of environmental legistation are very important. Carrying capacity is the one of effective tool which is formed with the aim of determination and measurement of the potential level of the use of source in different ecosystems and providing of the use of sustainable source in planning. In recent years, it is seen that for types of carrying capacity are studied. These are; 1. Ecological carrying capacity: The ability of standing of environmental sources against to pollution and crowding. 2. Physical carrying capacity: The amount of accommodation units, infrastructure, the facilities of transportation. 3. Social carrying capacity: The density that tourists and local people can stand. 4. Economic carrying capacity: The ability of standing of other sectors in tourism areas. Capacity levels are influenced by two major groups of factors. The first group are; 1. The characteristics of the tourists, 2. The characteristics of the destination area and its population. The second group are; 1. Natural environmental features and processes, 2. Economic structure and economic development, 3. Social structure and organization, 4. Political organization, 5. Level of tourist development. Difficulties in measuring and quantifying the thresholds of carrying capacities have restricted the use of carrying capacity as a planning tool. Some factors causing this restriction are; 1. That the acceptable levels of crowding can differ from one society to another, 2. That certain types of developments necessitate higher densities than others, even if the sizes of the developments are the same (beaches for relaxation vis-a-vis tourism), 3. That physical and environmental carrying capacities can be affected by management techniques. In Chapter 4, The types of alternative tourism which bring light to prevent or minimize negative impacts of tourism on the environment and its potentials in Turkey are studied. Soft tourism (alternative tourism) is a socially responsible, environmentally sensitive tourism approach. Due to having small scale and little density, it can be established by local organizations and economic income direclty belongs to local people. The main principles of soft tourism are as follows: 1. To conserve natural and cultural environmental values 2. To last spreading along the year instead of concentrated on definite seasons and area 3. To make use of existing buildings instead of new constructions 4. To protect traditional (local) arhitecture and organic development 5. To make use of a dynamic and active tourism strategy which contains the understanding of individual holiday 6. To depend on the environmental, social and economic carrying capacities of the destination areas. The types of soft tourism which can be developed also in Turkey in the principles of soft tourism can be grouped in this way: 1. Recreation Tourism 2. Mountain Tourism 3. Camping and Caravan Tourism 4. Pasture Tourism 5. Hunting Tourism 6. Yacht Tourism 7. Youth Tourism The facilities of accommodation in soft tourism, are as follows: 1. Houses for rent 2. Boarding houses (Pensions) 3. Camping 4. Mobile accomodations 5. Schools, dormitories In chapter 5, in settlement area and vicinity of İznik and lake surroundings, the potential impacts of proposal alternative tourism development and tourism buildings on the natural, built and socio-cultural environment and economic dimension are assessed, according to responses obtained with application to 12 persons of a questionnaire which is prepared making use of questionnaire used in Delphi. Persons who participated the questionnaire: civil engineer, mechanical technic painter, archaeologist, motel officer, hotel officer, headman, trader, resident in summer, officer from forest administration. At first, the potential environmental impacts of generally XI proposal alternative tourism development and tourism buildings in İznik are assessed and the results are shown in a table. Secondly, in settlement area and vicinity of îznik, the potentials of tourism buildings are defined and among of persons who defined the potential of each building, potential environmental impacts are assessed. The results are shown in a table. Thirdly, in lake surroudings, the potentials of tourism buildings are defined and environmental impacts are assessed. The results of it are shown in a table. Fourtly, in settlement area and vicinity of İznik, the potentials of proposal alternative tourism development and the environmental impacts of each tourism types are assessed. The results of it are shown in table. Fifthly, in lake surroundings, the potentials of proposal alternative tourism development are defined and the environmental impacts are assessed. The results are shown in a table. In Chapter 6, According to assessments obtained from questionnaires, a general conclusion is reached. The environmental impacts of proposal tourism development should be assessed before applying and according to the situation obtained in result of the assessment, planning decisions may be successful only if building and environment arrangements and tourism types which don't destroy natural and historical environments and have high quality aesthetic value, can be developed. This is an inevitable necessity in terms of both sustainable tourism and conservation of natural and historical values tourism depends on.
The Environmental impacts of tourism and assesment of alternative tourism development in İznik surraindings
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1994
Keywords: Bursa-İznik; Turizm; Bursa-İznik; Tourism